Pneumomediastinum in COVID-19: a phenotype of severe COVID-19 pneumonitis? The results of the UK POETIC survey. Issue 3 (1st September 2022) - Melhorn, James; Achaiah, Andrew; Conway, Francesca M.; Thompson, Elizabeth M.F.; Skyllberg, Erik W.; Durrant, Joseph; Hasan, Neda A.; Madani, Yasser; Naran, Prasheena; Vijayakumar, Bavithra; Tate, Matthew J.; Trevelyan, Gareth E.; et al.
Background: There is an emerging understanding that coronavirus disease 2019 (COVID-19) is associated with increased incidence of pneumomediastinum (PTM). We aimed to determine its incidence among patients hospitalised with COVID-19 in the UK and describe factors associated with outcome. Methods: A structured survey of PTM and its incidence was conducted from September 2020 to February 2021. UK-wide participation was solicited via respiratory research networks. Identified patients had severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and radiologically proven PTM. The primary outcomes were to determine incidence of PTM in COVID-19 and to investigate risk factors associated with patient mortality. Results: 377 cases of PTM in COVID-19 were identified from 58 484 inpatients with COVID-19 at 53 hospitals during the study period, giving an incidence of 0.64%. Overall 120-day mortality in COVID-19 PTM was 195 out of 377 (51.7%). PTM in COVID-19 was associated with high rates of mechanical ventilation. 172 out of 377 patients (45.6%) were mechanically ventilated at the point of diagnosis. Mechanical ventilation was the most important predictor of mortality in COVID-19 PTM at the time of diagnosis and thereafter (p<0.001), along with increasing age (p<0.01) and diabetes mellitus (p=0.08). Switching patients from continuous positive airway pressure support to oxygen or high-flow nasal oxygen after the diagnosis of PTM was not associated with difference in mortality. Conclusions: PTM appears to be a marker of severe COVID-19 pneumonitis. The majority of patients in whom PTM was identified had not been mechanically ventilated at the point of diagnosis. Roughly 0.6% of patients admitted with COVID-19 have pneumomediastinum identified. The finding is associated with severe COVID-19 and high mortality. https://bit.ly/3nXlaR5